2005
DOI: 10.1590/s0102-76382005000300014
|View full text |Cite
|
Sign up to set email alerts
|

Modificações no perfil do paciente submetido à operação de revascularização do miocárdio

Abstract: RBCCV Modificações no perfil do paciente submetido à operação de revascularização do miocárdio Changes in profile of patients submitted to coronary bypass graft surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1
5

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
3
8
1
5
Order By: Relevance
“…This study revealed similar results to those of national and international studies (13)(14) regarding gender, age and clinical data, most relevant comorbidities, and predominance of the male gender and smoking. These findings confirm that longevity, associated with preexisting conditions, increases the odds of health problems such as cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 88%
“…This study revealed similar results to those of national and international studies (13)(14) regarding gender, age and clinical data, most relevant comorbidities, and predominance of the male gender and smoking. These findings confirm that longevity, associated with preexisting conditions, increases the odds of health problems such as cardiovascular diseases.…”
Section: Discussionsupporting
confidence: 88%
“…The data here are compatible to previously published reports as patients who develop with coronary artery disease when young are characterized by the presence of the aforementioned risk factors amongst others including obesity, systemic arterial hypertension, diabetes mellitus, unfavorable lipid profile, high levels of apolipoprotein B and low levels of apolipoprotein AI [8]. It is also important to stress that currently the majority of patients submitted to coronary artery bypass surgery are old, male, smokers and in bad physical conditions [9]. A significant association between age, smoking, consumption of alcohol and serum fibrinogen was observed in this study, with older patients, smokers and alcoholics presenting with high serum fibrinogen concentrations.…”
Section: Discussionsupporting
confidence: 91%
“…However, surgeries are being performed on increasingly complex cases, thus leading to the development of complications following MRV, especially in the respiratory tract, such as those reported in this and in other studies [20][21][22] . Therefore, concomitantly with technological advances, there is a need to conduct better clinical assessments in light of the potential risk factors, seeking to further improve the status of the patient in the postoperative phase.…”
Section: Discussionmentioning
confidence: 75%